Effect of nitrogen on physical and optical properties of carbon films prepared by microwave plasma CVD for photovoltaic solar cells - Adhikary, Sunil (Scientific World, 2012)
Nitrogen doped amorphous carbon thin films were deposited on silicon and quartz substrates by microwave surface-wave plasma chemical vapour deposition (MW SWP CVD) to investigate effect of nitrogen on properties of the carbon films. Deposition rate of the films found in the range of 5-7.5 nm/min. Optical band gap of the films decreased from 3.3 eV to 2.3 eV corresponding to the increase of nitrogen flow rates from 0 to 10 sccm. RMS roughness of the undoped and Ndoped films was found to be 0.5 nm and 0.55 nm respectively suggesting that the amorphous carbon films deposited by MW SWP CVD are smooth. Scientific World, Vol. 10, No. 10, July 2012 p77-79 DOI: http://dx.doi.org/10.3126/sw.v10i10.6867